Price And Product Quality To Nexfood’s Purchase Intention - Daniel Chandra; Liliana Dewi (BIP's JURNAL BISNIS PERSPEKTIF, 2023)
The main purpose of this research is to measure the impact of price and product quality on purchase intention of Nexfood’s product. This research had distributed an online form purposive to be filled up by 97 participants from Surabaya. SPSS were used to analyzed data collected with multiple linear regression. To find the impact of independent variable to dependent variable simultaneously, this research was using the coefficient of determination. The price and product quality influencing the purchase intention in the amount of 58,6 percentage and the rest is influenced by other variable that wasn’t mentioned in this research. Based on the F-test, price and product quality simultaneously have a significant impact on purchase intention. Next, based on t-test, price and product quality partially have a significant impact on purchase intention. The finding of this research was price and product quality have a significant impact on purchase intention of Nexfood’s product. Based on that result, means that if the perception of price is increased then the purchase intention will also increase. If the perception of product quality is increased then the purchase intention will also increase. The results of this study serve as a reference for Nexfood to pay more attention to the prices set so that they can be more competitive with competing products, while also maintaining the quality of the products produced. What Nexfood can do is maintain prices without reducing the quality and portions of Nexfood products; maintaining prices and looking for new suppliers at lower prices so that consumers feel that Nexfood products are suitable and can compete with competitors; determine the price of Nexfood products in accordance with the benefits obtained by consumers.